Improving the cost-effectiveness of photographic screening for diabetic macular oedema: a prospective, multi-centre, UK study. Issue 8 (28th March 2014) - Prescott, Gordon; Sharp, Peter; Goatman, Keith; Scotland, Graham; Fleming, Alan; Philip, Sam; Staff, Roger; Santiago, Cynthia; Borooah, Shyamanga; Broadbent, Deborah; Chong, Victor; Dodson, Paul; et al.
Abstract : Background/aims: Retinal screening programmes in England and Scotland have similar photographic grading schemes for background (non-proliferative) and proliferative diabetic retinopathy, but diverge over maculopathy. We looked for the most cost-effective method of identifying diabetic macular oedema from retinal photographs including the role of automated grading and optical coherence tomography, a technology that directly visualises oedema. Methods: Patients from seven UK centres were recruited. The following features in at least one eye were required for enrolment: microaneurysms/dot haemorrhages or blot haemorrhages within one disc diameter, or exudates within one or two disc diameters of the centre of the macula. Subjects had optical coherence tomography and digital photography. Manual and automated grading schemes were evaluated. Costs and QALYs were modelled using microsimulation techniques. Results: 3540 patients were recruited, 3170 were analysed. For diabetic macular oedema, England's scheme had a sensitivity of 72.6% and specificity of 66.8%; Scotland's had a sensitivity of 59.5% and specificity of 79.0%. When applying a ceiling ratio of £30 000 per quality adjusted life years (QALY) gained, Scotland's scheme was preferred. Assuming automated grading could be implemented without increasing grading costs, automation produced a greater number of QALYS for a lower cost than England's scheme, but was not cost effective, at the study's operating point, compared with Scotland's. The addition of optical coherence tomography, to each scheme, resulted in cost savings without reducing health benefits. Conclusions: Retinal screening programmes in the UK should reconsider the screening pathway to make best use of existing and new technologies.